Comparative Proteome Profiling during Cardiac Hypertrophy and Myocardial Infarction Reveals Altered Glucose Oxidation by Differential Activation of Pyruvate Dehydrogenase E1 Component Subunit β. Issue 11 (5th June 2015) - Mitra, Arkadeep; Basak, Trayambak; Ahmad, Shadab; Datta, Kaberi; Datta, Ritwik; Sengupta, Shantanu; Sarkar, Sagartirtha
Abstract: Cardiac hypertrophy and myocardial infarction (MI) are two etiologically different disease forms with varied pathological characteristics. However, the precise molecular mechanisms and specific causal proteins associated with these diseases are obscure to date. In this study, a comparative cardiac proteome profiling was performed in Wistar rat models for diseased and control (sham) groups using two-dimensional difference gel electrophoresis followed by matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry. Proteins were identified using Protein Pilot™ software (version 4.0) and were subjected to stringent statistical analysis. Alteration of key proteins was validated by Western blot analysis. The differentially expressed protein sets identified in this study were associated with different functional groups, involving various metabolic pathways, stress responses, cytoskeletal organization, apoptotic signaling and other miscellaneous functions. It was further deciphered that altered energy metabolism during hypertrophy in comparison to MI may be predominantly attributed to induced glucose oxidation level, via reduced phosphorylation of pyruvate dehydrogenase E1 component subunit β (PDHE1-B) protein during hypertrophy. This study reports for the first time the global changes in rat cardiac proteome during two etiologically different cardiac diseases and identifies key signaling regulators modulating ontogeny of these two diseases culminating in heart failure. This study also pointed toward differential activation of PDHE1-B that accounts for upregulation of glucose oxidation during hypertrophy. Downstream analysis of altered proteome and the associated modulators would enhance our present knowledge regarding altered pathophysiology of these two etiologically different cardiac disease forms. Graphical Abstract: Highlights: Cardiac hypertrophy and MI are etiologically different cardiac disease forms. Comparative proteomics revealed alteration of global proteome between them. Differential activation of PDHE1-B was found. Altered metabolic profile was observed during hypertrophy and MI. Differential molecular milieu accounts for different cardiac pathophysiologies.